Influence of the catenary parameter (H/w) on the fatigue life of overhead conductors. (April 2017) - Kalombo, R.B.; Pestana, M.S.; Ferreira, J.L.A.; da Silva, C.R.M.; Araújo, J.A.
Abstract: The main objective of this paper is to generate new experimental data to allow a comparative study on the effects of the catenary parameter ( H/w ) in the fretting fatigue life of overhead conductors. A battery of thirty six fatigue tests was carried out on a 900 MCM All Aluminium Alloy Conductor (AAAC 900 MCM) and on a Tern Aluminium Conductor Steel Reinforced (ACSR Tern). The H/w parameter is defined as the ratio between the initial horizontal tensile load, H, and the conductor weight per unit length, w . Two different H/w values were considered in this study, 1820 and 2144 m. Comparisons proved that the ACSR Tern conductor could sustain a significantly higher number of cycles before fatigue failure than the AAAC 900 MCM for both values of H/w . Failure analysis of the broken samples revealed not only that cracks initiated in the fretted areas of the aluminium wires for both types of cables, but also that the AAAC 900 MCM wires presented quasi-planar fracture with significant crack propagation, while a 45 degrees ductile fracture predominated in the ACSR Tern. Highlights: New experimental data to evaluate the effects of the parameter (H/w) on the fretting fatigue life of AAAC 900 MCM and of ACSR Tern conductors. For a same value of H/w, the ACSR Tern sustained a significantly higher life than the AAAC 900 MCM, independently of the level of stress amplitude considered. The AAAC 900 MCM wires presented quasi planar fracture with significant crack propagation, while a 45° ductile fracture predominated in the ACSR Tern. Actual strains/stress in the wires can in fact be approximated by a linear function of H/w.